Characterization of the Functional Roles of Histidine-Rich Glycoprotein in Coagulation - Vu, Trang (My University, 2014)
Histidine-rich glycoprotein (HRG) is a protein present in plasma at ~ 2 μM, but whose physiologic function is unclear. HRG is a multi-domain protein that contains a unique histidine-rich core that interacts with zinc and hydrogen ions to modulate ligand binding. Due to its modular structure and capacity to sense local changes in zinc and pH, HRG binds several ligands including complement proteins, phospholipids, DNA, fibrin(ogen), heparin, factor (F) XIIa and plasmin. Thus, it is hypothesized that HRG functions as an accessory or adapter protein that bridges different ligands together. Despite the array of ligands and potential involvement in immunity, angiogenesis, coagulation and fibrinolysis, no clear role for HRG has emerged. Congenital HRG deficiency in humans has been associated with a variable phenotype; some investigators report increased susceptibility to thrombosis while others do not. However, studies in HRG-deficient mice reveal that HRG attenuates coagulation. Coagulation is initiated via the intrinsic (or contact) and extrinsic (or tissue factor) pathways and culminates in the generation of thrombin. Thrombin catalyzes the conversion of fibrinogen into a fibrin meshwork that reinforces the platelet plug at sites of vascular injury. There are two circulating isoforms of fibrinogen that differ with respect to their γ-chains. Bulk fibrinogen is composed of a pair of γA-chains, and is designated γA/γA-fibrinogen, whereas a minor variant contains a γA-chain and a γʹ-chain, and is designated γA/γʹ-fibrinogen. The γʹ-chain contains an anionic 20-amino acid residue extension at its COOH-terminus, which provides an accessory binding site for thrombin. Thrombin possesses an anion binding pocket termed exosite II that flanks the active site and mediates its interaction with the γʹ-chain of fibrinogen. Exosite II is an evolutionary feature that is unique to thrombin, as this region is not observed on the prototypic serine protease trypsin or on other defibrinogenating enzymes from snake venom such as batroxobin. Although the physiologic function of the thrombin-γʹ-chain interaction is unclear, it is proposed that this interaction modulates thrombin’s activity when it is bound to fibrin clots. Consistent with this, we show that γA/γʹ-fibrin attenuates thrombin’s capacity to promote clot expansion compared with thrombin bound to γA/γA-fibrin clots, thereby demonstrating that γA/γʹ-fibrin attenuates thrombin’s activity. In the presence of physiologic concentrations of zinc, HRG binds the γʹ-chain of fibrino(gen) and competes with thrombin for binding, thereby suggesting that HRG is a unique modulator of thrombin activity on fibrin clots. Platelets store zinc and HRG in their α-granules and release both components when they undergo activation at sites of injury, which localizes HRG in the vicinity of fibrin-bound thrombin. Consistent with the role of HRG in modulating coagulation, we also show that HRG attenuates contact activation of coagulation, but has no impact on clotting initiated by the extrinsic pathway. The intrinsic pathway is initiated when FXII is activated by polyanions such as RNA and DNA, which are released into the blood after cellular activation, injury or death. FXIIa activates FXI, thereby propagating coagulation and leading to thrombin generation and fibrin formation. Recently, studies using rodent, rabbit and non-human primate models of thrombosis have shown that knock down of FXII or FXI with antisense oligonucleotides or blocking FXIIa or FXIa activity with inhibitors attenuates thrombosis, while having a minimal impact on hemostasis. With increasing evidence that the intrinsic pathway plays an important role in thrombosis, FXII and FXI have emerged as prominent targets for new anticoagulants. However, little is known about how the intrinsic pathway is regulated, so as to prevent uncontrolled clotting. HRG attenuates the intrinsic pathway by binding both FXIIa and the contact activators, RNA and DNA. By binding nucleic acids, HRG is localized to the site of contact activation, where it is poised to inhibit FXIIa. HRG binds to an allosteric region on FXIIa and attenuates its capacity to feedback activate FXII and to activate FXI, thereby inhibiting the initiating steps of contact activation. In addition, HRG attenuates the cofactor role of RNA and DNA in thrombin activation of FXI, which is an important feedback step. With the capacity to modulate multiple steps in the intrinsic pathway, HRG likely serves as a dynamic regulator of contact activation. We tested our hypothesis that HRG is a novel inhibitor of the intrinsic pathway in a murine model of FeCl3-induced arterial injury. HRG-deficient mice exhibit accelerated thrombosis compared with wild type controls, an effect that was abolished by repletion with human HRG. Therefore, these studies indicate that HRG deficiency induces a prothrombotic phenotype. Consistent with the role of HRG as a modulator of the intrinsic pathway, we show that thrombosis after the FeCl3-induced arterial injury is attenuated by administration of RNase, but not DNase, or by knock down of FXII, but not FVII. Therefore, these studies show that thrombosis in this model is induced by RNA and occurs in a FXII-dependent manner. Furthermore, blood loss after tail tip amputation is similar in HRG-deficient and wild type mice, demonstrating that HRG does not modulate hemostasis. Therefore, these studies suggest that HRG is a dynamic regulator of the intrinsic pathway, and acts as a molecular brake to limit procoagulant stimuli. The observations that HRG binds fibrin(ogen), FXIIa and nucleic acids and modulates the thrombin-γʹ-interaction and intrinsic pathway of coagulation, suggest that HRG is a key regulator of coagulation. HRG, the contact system and fibrin are also important in the innate immune response, demonstrating that the interaction of HRG with these factors may provide a unique link between coagulation and immunity. Since immune cells and the coagulation system contribute to both deep vein thrombosis and sepsis, further characterization of the role of HRG in these conditions will contribute to a better understanding of the pathophysiological role of HRG, and may identify novel therapeutic directions.
Keywords: Coagulation; Thrombosis; Histidine-rich glycoprotein; Nucleic acids; Fibrinogen; Factor XII; Batroxobin; Thrombin